Evaluation of anti-ulcer and ulcerative colitis of Sonchus oleraceus L - Esraa A. Alothman; Amani S. Awaad; Amal A. Safhi; Shekhah S. Almoqren; Reham M. El-Meligy; Yara M. Zain; Fatmah A. Alasmary; Saleh I. Alqasoumi (Elsevier, 2018)
Sonchus oleraceus L. was evaluated for its gastro antiulcerogenic and anti-ulcerative colitis activities Different extracts and fractions from Sonchus oleraceus aerial parts and roots were evaluated at different dose; total alcohol extracts of aerial parts SA and roots SR were evaluated doses 250 & 500 mg/kg, While Successive extracts (SAL, SRL, CSA, CSR, BSA & BSR) were evaluated at dose of 150 mg/kg. Absolute ethanol-induced ulcer model was used for evaluation of the anti-ulcerogenic activity. The root extract showed promising antiulcerogenic activity as the total alcohol extract of the root SR (500 mg/kg) produced 88.5% protection from control ulcer which is significantly more effective than the standard drug omeprazole (20 mg/kg), in addition, the butanol fraction of the root extract BSR also produced 76.66% protection from control ulcer. On the other hand, the aerial parts total extract SA showed low antiulcerogenic activity in both tested doses (250 & 500 mg/kg) as it produced 25% & 28.33% protection from control ulcer respectively. Only the butanol fraction of the aerial parts extract BSA showed promising activity 54.16%. In the acetic acid-induced ulcerative colitis model, among the investigated extracts of Sonchus oleraceus; only the total extract of the aerial parts (SA) at dose 500 mg/kg showed strong anti-ulcerative colitis activity and this activity is followed by the activity of the butanol and chloroform fractions of the aerial parts, they produced 77.28%, 57.4% & 47.68% protection from control colitis respectively. The standard drug dexamethasone produced 63.36% protection from control colitis. The total alcohol extracts SR & SA showed no alteration on liver and kidney functions and these extracts are safe up to 5000 mg/kg. Phytochemical screening of the investigated extracts revealed the presence of carbohydrates, flavonoids, tannins, unsaturated sterols, proteins and lactones which could be responsible for the activities. Keywords: Peptic ulcer, Liver function, Kidney function, Acute toxicity, Asteraceae, Phytochemical screening